2011
DOI: 10.1053/j.gastro.2011.08.048
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl d-Aspartate Channels Link Ammonia and Epithelial Cell Death Mechanisms in Helicobacter pylori Infection

Abstract: BACKGROUND & AIMS Helicobacter pylori infection is a risk factor for gastric cancer. Ammonia/ammonium (A/A) is a cytotoxin generated by H pylori that kills gastric epithelial cells. We investigated whether A/A cytotoxicity occurs by activating N-methyl D-aspartate (NMDA) channels, which results in Ca2+ permeation and epithelial cell death. METHODS Gastric epithelial cells were cultured to confluence and then incubated with A/A and NMDA channel or cell signaling antagonists. Cells were incubated with wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…It has been shown previously that ammonia can induce oxidative stress, cell swelling, and mitochondrial damage in astrocytes and epithelial cells (21,22,29). In the current study, we found that ammonia could induce oxidative stress and mitochondrial damage in DCs, and that this mitochondrial damage could be ameliorated by ROS control.…”
Section: Discussionsupporting
confidence: 69%
“…It has been shown previously that ammonia can induce oxidative stress, cell swelling, and mitochondrial damage in astrocytes and epithelial cells (21,22,29). In the current study, we found that ammonia could induce oxidative stress and mitochondrial damage in DCs, and that this mitochondrial damage could be ameliorated by ROS control.…”
Section: Discussionsupporting
confidence: 69%
“…Generally speaking, the NMDAR channel is opened by glutamate; however, there is also a voltage‐sensitive component to gating such as by ammonia, as shown in several studies . Given the direct contact between the colonic mucosal cells and the luminal environment, we measured both the glutamate and ammonia levels in all fecal samples from the TNBS‐treated mice and the mice in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The ammonia product of this alternative reaction can be directly antibacterial if it saponifies bacterial lipids (18)(19)(20). Alternatively, as first shown for Helicobacter pylori, ammonia kills infected human cells that express the NMDA receptor (21). Given the negative implications of the ammonia-generating β-elimination reaction, it is unsurprising that it is biochemically curtailed in two ways.…”
Section: Significancementioning
confidence: 99%